Comparative Study of Antibacterial Effects of Titanium Dioxide Nanoparticles Alone and in Combination with Antibiotics on MDR Pseudomonas aeruginosa Strains - Ahmed, Fatma Y (Int J Nanomedicine, 2020)
INTRODUCTION: The efficacy of several antimicrobial agents has been hindered due to the increasing frequency of ﻿multidrug-﻿resistant (MDR) Pseudomonas aeruginosa strains. So, the need for new antibacterial drugs or drug combinations is urgent. Recently, desirable antibacterial effects were reported for many metals nanoparticles such as TiO(2) ﻿nanoparticles (TDNs). PURPOSE: This study aims to investigate the prevalence of MDR P. aeruginosa and assess the efficiency of TDN in the treatment of MDR P. aeruginosa-associated infections. MATERIALS AND METHODS: The synthesis of TDN by the sol-gel method was carried out. Particle size measurements and morphology were done using ﻿dynamic ﻿light ﻿scattering (DLS) and ﻿high-﻿resolution ﻿transmission ﻿electron ﻿microscopy (HR-TEM). To investigate the physical and chemical changes of drugs due to the combination, the tested drugs, both alone and in combination with TDN, were subjected to ﻿differential ﻿scanning ﻿calorimetry (DSC), ﻿infrared (IR) spectroscopy, and X-ray diffraction studies. Antimicrobial susceptibility was detected by agar disc﻿-diffusion assay. The minimum inhibitory concentration (MIC) of TDN and the tested antibiotics were assessed by the agar dilution method. Checkerboard analysis was performed to determine the combined effect of TDN and the tested antibiotics against 25 MDR P. aeruginosa strains. RESULTS: TDNs ﻿were prepared with an average particle size of 64.77 ± 0.14 nm with an accepted polydispersity ﻿index (PDI) value of 0.274 ± 0.004. TEM showed that the particles were shaped into irregular spheres. Twenty-five P. aeruginosa isolates that were absolutely resistant to ﻿cefepime (100%), highly resistant to ﻿ceftriaxone (96%), ﻿amikacin (80%), and ﻿ciprofloxacin (76%) were selected. Superior antibacterial activity of TDN was observed against the selected 25 MDR P. aeruginosa isolates. The combination of TDN and ﻿cefepime were found to show synergistic activity against all tested isolates followed by ﻿ceftriaxone (96%), ﻿amikacin (88%), and ﻿ciprofloxacin (80%). CONCLUSION: Using TDN in combination with antibiotics can help in the treatment of MDR P. aeruginosa-associated infections. So, preparation of topical pharmaceutical dosage forms containing a combination of these antibiotics and TDN can be useful against MDR P. aeruginosa.